Relative risk aversion and business fluctuations - Ken'ichi Hashimoto; Ryonghun Im; Takuma Kunieda; Akihisa Shibata (Osaka University, Institute of Social and Economic Research (ISER), 2025)
By applying a simple dynamic general equilibrium model without exogenous shocks inhabited by infinitely lived capitalists and workers, we show that a higher degree of relative risk aversion can destabilize an economy. In traditional real business cycle (RBC) theory, a higher degree of relative risk aversion dampens the amplitude of the consumption fluctuations caused by exogenous shocks through consumption smoothing. However, a higher degree of relative risk aversion combined with a high degree of elasticity of the marginal product of capital can also lead to the emergence of a nonlinear mechanism that causes endogenous business fluctuations. The nontrivial steady state loses stability due to the higher degree of relative risk aversion; thus, endogenous business fluctuations can occur. This result suggests that for a deeper understanding of boom-bust cycles, researchers should merge exogenous and endogenous business fluctuations when investigating economies.
Keywords: E1; E2; E3; 330; endogenous business fluctuations; relative risk aversion; dynamic general equilibrium; instability